(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Państwa tradycyjnie bardzo niechętnie odnoszą się do jakichkolwiek ograniczeń swobody uznawania określonych faktów prawnych i ich skutków na płaszczyźnie międzynarodowej. Tym niemniej w ciągu ostatnich kilkudziesięciu lat miało miejsce co najmniej kilkanaście przypadków, w których wszystkie bądź niemal wszystkie państwa świata przedsięwzięły wspólnie kroki zmierzające do niedopuszczenia do uznania konkretnych zdarzeń tego rodzaju i wynikających z nich konsekwencji. Działania te były podejmowane przede wszystkim w ramach organizacji międzynarodowych o charakterze uniwersalnym i przejawiały się w formie określanej w doktrynie jako zbiorowa odmowa uznania (zbiorowe nieuznawanie). Wśród nich istotną grupę obejmują przypadki zbiorowej odmowy uznania państw, które są przedmiotem niniejszej pracy. The article aims to study the cases of collective non-recognition of certain States by the League of Nations and the United Nations, and to determine the legal basis of the measures adopted. The author divides the legal grounds for non-recognition into substantive and formal ones. In the course of the case study, four substantive grounds are identified, more than one of which was violated during the process of creation of each non-recognized State: the ban on the use of force, the territorial integrity of States, the right to self-determination and the prohibition of apartheid and racial discrimination. The examination of formal grounds reveals that the virtually universal compliance with UN calls might have been driven not only by binding resolutions but also by the treaties, customary norms and peremptory norms, binding different UN members and nonmembers to a varying extent. Still, since the non-recognized States were neither members of the UN nor were bound by respective treaties, the illegality of their creation may only be explained with reference to violation of the peremptory norms and, in some cases, of the customary norms of international law.